Free Cash Flows, Management Ownership, Dividend Policy, and Debt Policy - Ardhya Yudistira Adi Nanggala (Universitas Jember, 2020)
This study aims to identify and examine empirically effect of free cash flows, managerial ownership and dividend policy on debt policy (empirical study on companies listed on Stock Exchange). This study uses secondary data in form of financial statements derived from annual financial statements of companies listed on Stock Exchange and available reporting consecutive years from 2012 to 2017. Samples were taken by purposive sampling with first criteria company's annual financial statement data available for consecutive reporting years from 2012 to 2017. Number of samples in this study 132 firm years. Data analysis methods used in this study is multiple linear regression analysis. Results showed that: free cash flows and managerial ownership has a significant positive effect on debt policy. Dividend policy have a significant negative effect on debt policy. Keywords: Free cash Flows, Management Ownership Dividend Policy, Debt Policy